Polyimide-containing heat-resistant release sheet and method for pressure molding of object to be molded
By using polyamide heat-resistant release sheet made of bisphenol tetramethyl diamide and bisamylamide derived structural units, the problems of insufficient mechanical strength and poor replication under high temperature and high pressure in the prior art are solved, and the improvement of high precision, high replication and mechanical strength is achieved.
Patent Information
- Application Number
- JP2022536481
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-27
- Filing Date
- 2021-07-06
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-07-06
AI Technical Summary
When used under high temperature and high pressure, the mechanical strength is insufficient, resulting in deformation of the shape during reuse and uneven thickness leads to poor reproducibility of the mold product.
The polyamide heat-resistant release sheet made of bisphenol tetramethyldiamide and bisaminoamide derived structural units is used. The material has high mechanical strength, low surface roughness and low thickness unevenness, meeting specific dimensional stability requirements.
It realizes high precision and high replication of mold products when used under high temperature and high pressure conditions, and the mechanical strength and dimensional stability of the release sheet are significantly improved, extending the service life.
Smart Images

Figure 0007671440000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyimide-containing heat-resistant release sheet and a method for pressing a workpiece using the polyimide-containing heat-resistant release sheet. [Background technology]
[0002] Hot plate presses, roll laminators, double belt presses, etc. are devices that are widely used in molding and lamination. Methods using hot plate presses and double belts are known as devices for performing molding and lamination. The hot plate press method is a method in which a pair of release-treated steel sheets or resin sheet materials with excellent release properties, such as fluororesin sheet materials, are used as carrier sheets (transport sheets), a workpiece is sandwiched between the carrier sheets, and the workpiece is sent between heated presses to apply pressure for a predetermined time. The double belt method is a method in which a carrier sheet and a workpiece are continuously sent between a pair of endless steel belts, and pressure is applied while heating and moving the workpiece while sandwiched between the belts. In such devices, a release sheet is used to prevent the pressurized body and the workpiece (molded object, laminated object) from adhering to each other during molding and lamination. In particular, a heat-resistant release sheet with excellent heat resistance and mechanical strength is required for molding and lamination at high temperatures and high pressures.
[0003] Conventionally, many proposals have been made for these release sheets. Silicone rubber sheets, fluororesin sheets, etc. are widely used as heat-resistant release sheets. Such silicone rubber sheets and fluororesin sheets have poor mechanical strength, and gradually deform when used repeatedly, making it difficult to obtain molded products with good reproducibility. In addition, due to low thickness accuracy, the molded product is prone to thickness unevenness, and does not necessarily meet high-precision requirements. Furthermore, silicone rubber sheets and fluororesins do not necessarily have sufficient durability at high temperatures, and when used for a long period of time, the resin components deteriorate and decompose, causing the relatively low molecular weight silicone resin or fluororesin to migrate to the surface of the molded product, resulting in various problems. In addition, under normal circumstances, the carrier sheet contains a fair amount of moisture, and when the temperature rises, the moisture evaporates from the carrier sheet. The resulting dimensional changes cause the molded object to be pulled by the carrier sheet, often causing wrinkles and other problems.
[0004] In order to solve these problems, many proposals have been made in recent years. For example, a release sheet formed by laminating an ethylene-tetrafluoroethylene copolymer film on one side of a metal plate having a thickness of 0.05 to 0.5 mm (see Patent Document 1), a release sheet equipped with a sheet substrate and a release layer coated on the surface of the sheet substrate, the release layer containing a fluororesin and an acrylic resin (see Patent Document 2), a heat-resistant release sheet having a resin layer having heat resistance and releasability on one or both sides of an expanded graphite sheet, the resin layer being made of a thermosetting polyimide resin or a fluororesin (see Patent Document 3), and the like have been proposed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2000-062089 A [Patent Document 2] JP 2000-290897 A [Patent Document 3] JP 2003-127267 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, even these release sheets have problems such as a decrease in reproducibility of molded products due to repeated use.
[0007] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a polyimide-containing heat-resistant release sheet that can produce molded products with high precision and good reproducibility even when used repeatedly, and to provide a method for pressurizing a workpiece using the polyimide-containing heat-resistant release sheet. [Means for solving the problem]
[0008] The present inventors have conducted extensive research into a polyimide-containing heat-resistant release sheet and a method for pressurizing a workpiece using the polyimide-containing heat-resistant release sheet. As a result, they have found that by employing the following configuration, even when the sheet is used repeatedly, a molded product can be obtained with high precision and good reproducibility, and have completed the present invention.
[0009] That is, the present invention provides the following. (1) Having structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide, The average thickness unevenness is 5% or less. The surface roughness Ra is 0.05 μm or less. The tensile modulus is 6 GPa or more, A polyimide-containing heat-resistant release sheet, characterized in that the following formula (1) is satisfied: 100×|A1-A2| / A0<0.004 Formula (1) (Here, A0 is the dimension of the polyimide-containing heat-resistant release sheet at 25°C before heating, A1 is the dimension when heated from 25°C to 150°C and returned to 25°C, and A2 is the dimension when, after measuring the dimension A1, it is heated again to 150°C and returned to 25°C.)
[0010] According to the above-mentioned configuration, since the structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide are contained, the dimensional change due to water evaporation is small, and it is possible to satisfy the following formula (1): In addition, since the structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide are contained, by suitably adjusting the conditions for forming into a sheet (particularly the imidization conditions), it is easy to obtain favorable physical properties as a release sheet, such as uneven thickness, surface roughness, and tensile modulus. In addition, since the average thickness unevenness is 5% or less, if the release sheet is sandwiched between the workpiece and a press plate or the like and pressure processed, the difference in shape between multiple workpieces is small. In addition, since the average thickness unevenness is 5% or less, if the release sheet is sandwiched between the workpiece and a press plate or the like and pressure processed, the thickness unevenness within the workpiece in one processing can be reduced. In other words, a molded product can be obtained with high precision and good reproducibility. In addition, since the surface roughness Ra is 0.05 μm or less, when the release sheet is sandwiched between the workpiece and a press plate or the like and subjected to pressure processing, the surface shape of the release sheet (irregularities caused by the surface roughness) can be prevented from being transferred to the workpiece. As a result, a molded product can be obtained with high accuracy and good reproducibility. In addition, since the tensile modulus is 6 GPa or more, the mechanical strength is good. Therefore, when the release sheet is sandwiched between the workpiece and a press plate or the like and subjected to pressure processing, deformation is unlikely to occur even if it is used repeatedly. As a result, even if it is used repeatedly, a molded product can be obtained with high precision and good reproducibility. In addition, since the value of "100 x |A1-A2| / A0" is less than 0.04, when the release sheet is sandwiched between the workpiece and a press plate or the like and subjected to pressure processing, moisture evaporates from the release sheet when the temperature rises, which can suppress the accompanying dimensional changes. As a result, it is possible to suppress the workpiece from being pulled by the release sheet, which can cause wrinkles, etc. Thus, according to the present invention, the release sheet has structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide, has an average thickness unevenness of 5% or less, a surface roughness Ra of 0.05 μm or less, and a tensile modulus of elasticity of 6 GPa or more, and satisfies the above formula (1). Therefore, when the release sheet is sandwiched between a workpiece and a press plate or the like and subjected to pressure processing, a molded product can be obtained with high precision and good reproducibility even when used repeatedly.
[0011] (2) In the configuration (1) above, the linear thermal expansion coefficient is preferably 6 ppm / K or less.
[0012] A coefficient of linear expansion (CTE) of 6 ppm / K or less can be said to have better dimensional stability (heat resistance), which makes it possible to obtain molded products with higher accuracy and reproducibility.
[0013] The present invention also provides the following. (3) pressing the workpiece between the polyimide-containing heat-resistant release sheets, The polyimide-containing heat-resistant release sheet is The compound has structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide, The average thickness unevenness is 5% or less. The surface roughness Ra is 0.05 μm or less. The tensile modulus is 6 GPa or more, A method for pressurizing a workpiece, characterized in that the following formula (1) is satisfied: 100×|A1-A2| / A0<0.004 Formula (1) (Here, A0 is the dimension of the polyimide-containing heat-resistant release sheet at 25°C before heating, A1 is the dimension when heated from 25°C to 150°C and returned to 25°C, and A2 is the dimension when, after measuring the dimension A1, it is heated again to 150°C and returned to 25°C.)
[0014] According to the above-mentioned configuration, since the workpiece is pressurized using the polyimide-containing heat-resistant release sheet, a molded product can be obtained with high precision and good reproducibility. Effect of the Invention
[0015] According to the present invention, it is possible to provide a polyimide-containing heat-resistant release sheet that can produce molded products with high precision and good reproducibility even when used repeatedly, and a method for pressurizing a workpiece using the polyimide-containing heat-resistant release sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described.
[0017] <Polyimide-containing heat-resistant release sheet> The polyimide-containing heat-resistant release sheet according to this embodiment (hereinafter also referred to as "release sheet" or "polyimide film") is The compound has structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide, The average thickness unevenness is 5% or less. The surface roughness Ra is 0.05 μm or less. The tensile modulus is 6 GPa or more, The following formula (1) is satisfied. 100×|A1-A2| / A0<0.004 Formula (1) (Here, A0 is the dimension of the polyimide-containing heat-resistant release sheet at 25°C before heating, A1 is the dimension when heated from 25°C to 150°C and returned to 25°C, and A2 is the dimension when, after measuring the dimension A1, it is heated again to 150°C and returned to 25°C.)
[0018] The release sheet is a polyimide film having structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide.
[0019] Generally, a polyimide film is obtained by applying a polyamic acid (polyimide precursor) solution obtained by reacting diamines and tetracarboxylic acids in a solvent to a support for preparing a polyimide film, drying the solution to form a green film (hereinafter also referred to as a "precursor film" or "polyamic acid film"). The green film is then subjected to high-temperature heat treatment on the support for preparing a polyimide film or in a state where it is peeled off from the support to cause a dehydration ring-closing reaction. Here, the green film refers to a polyamic acid film containing a solvent and having self-supporting properties. The solvent content of the green film is not particularly limited as long as it has self-supporting properties, but is preferably 1% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, even more preferably 20% by mass or more, and particularly preferably 30% by mass or more. In addition, the solvent content is preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less, and particularly preferably 50% by mass or less. Alternatively, the polyimide film may be obtained by applying a polyimide solution obtained by a dehydration ring-closing reaction between diamines and tetracarboxylic acids in a solvent to a support for preparing a polyimide film, drying the solution to obtain a polyimide film containing, for example, 1 to 50 mass % of a solvent, and further drying the polyimide film containing 1 to 50 mass % of a solvent at a high temperature on the support for preparing a polyimide film or after peeling the polyimide film from the support.
[0020] In this embodiment, diaminobenzanilide is used as the diamine for obtaining the release sheet. As the diaminobenzanilide, 4,4'-diaminobenzanilide (hereinafter, also referred to as DABAN) is preferable.
[0021] The content of the diaminobenzanilide (particularly, DABAN) is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 100% by mass, when the total diamine components are 100% by mass.
[0022] The diamines other than the diaminobenzanilide are not particularly limited, and aromatic diamines, aliphatic diamines, alicyclic diamines, etc., which are usually used in polyimide synthesis, can be used.
[0023] In the present embodiment, biphenyltetracarboxylic dianhydride is used as the tetracarboxylic acid for obtaining the release sheet. As the biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride (hereinafter, also referred to as BPDA) is preferable.
[0024] The content of the biphenyltetracarboxylic dianhydride (particularly, BPDA) is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 100% by mass, when the total amount of the tetracarboxylic acid components is 100% by mass.
[0025] The tetracarboxylic acids other than the biphenyltetracarboxylic dianhydride are not particularly limited, and aromatic tetracarboxylic acids (including their acid anhydrides), aliphatic tetracarboxylic acids (including their acid anhydrides), and alicyclic tetracarboxylic acids (including their acid anhydrides) that are usually used in polyimide synthesis can be used. When these are acid anhydrides, they may have one or two anhydride structures in the molecule, but preferably have two anhydride structures (dianhydrides).
[0026] As described above, the release sheet uses diaminobenzanilide as the diamine and biphenyltetracarboxylic dianhydride as the tetracarboxylic acid to obtain the release sheet, and therefore the release sheet has structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide.
[0027] The release sheet preferably has structural units derived from BPDA and DABAN, and when the total structural units contained in the release sheet is taken as 100% by mass, the total of the structural units derived from BPDA and DABAN is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 100% by mass.
[0028] The release sheet may contain a composition other than the polyimide having structural units derived from BPDA and DABAN. The content of the polyimide (polyimide having structural units derived from BPDA and DABAN) contained in the release sheet is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, and may be 100% by mass. The composition other than the polyimide having structural units derived from BPDA and DABAN is not particularly limited as long as it is not contrary to the spirit of the present invention, and those typically used in polyimide-based release sheets can be used.
[0029] The release sheet has structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide, and therefore has good physical properties as a release sheet in terms of thickness unevenness, surface roughness, and tensile modulus, which the inventors presume is due to the high orientation of the structural units when the sheet is made. In addition, the physical properties such as thickness unevenness, surface roughness, and tensile modulus of elasticity are excellent as a release sheet due to the presence of structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide, but as will be described later, the physical properties can be further controlled to be excellent by the conditions for forming the sheet (particularly the imidization conditions).
[0030] The release sheet has an average thickness unevenness of 5% or less. The average thickness unevenness is preferably 4.5% or less, more preferably 4% or less, and even more preferably 3.5% or less. The lower limit of the average thickness unevenness is not particularly limited, but for molding and lamination applications, it is, for example, 0.5% or more, 1% or more, etc. Since the average thickness unevenness is 5% or less, if the release sheet is sandwiched between a workpiece and a press plate or the like and pressurized, the difference in shape between multiple workpieces is reduced. In addition, since the average thickness unevenness is 5% or less, if the release sheet is sandwiched between a workpiece and a press plate or the like and pressurized, the thickness unevenness in the workpiece in one processing can be reduced. In other words, a molded product can be obtained with high precision and good reproducibility. Methods for controlling the average thickness unevenness to 5% or less include employing a structure having structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide as the structure of the release sheet, and appropriately controlling the conditions (particularly the imidization conditions) when forming the sheet.
[0031] In this specification, the average thickness unevenness refers to a value determined by the following method. <How to determine the average thickness unevenness: When the release sheet is in roll form> Cut out a strip of sample from near the center of the transverse direction (TD). The strip size is 5 cm wide and 5 cm long. Then, cut out four strips at 1 m intervals in the longitudinal direction (MD) to obtain a total of five samples. For each strip, the thickness is measured at five points in total: the centre, two points 5 cm apart along the length from the centre, and two points 10 cm apart. For each strip, the thickness variation is calculated using the following calculation. Thickness unevenness = 100 x (maximum thickness - minimum thickness) / (average thickness) Finally, the thickness variations of the five strips are averaged, and this is taken as the average thickness variation value. <How to calculate the average thickness unevenness: When the release sheet is rectangular (sheet)> The thickness is measured at five points in total: four corners and one in the center. The four corners are measured at points 10 cm away from the two nearest sides. The thicknesses at the five locations are averaged and this is regarded as the average thickness unevenness.
[0032] The release sheet has a surface roughness Ra of 0.05 μm or less. The surface roughness Ra is preferably 0.04 μm or less, more preferably 0.03 μm or less, and even more preferably 0.025 μm or less. The lower limit of the surface roughness Ra is not particularly limited, but for molding and lamination applications, it is, for example, 0.001 μm or more, 0.002 μm or more, etc. Since the surface roughness Ra is 0.05 μm or less, if the release sheet is sandwiched between a workpiece and a press plate or the like and subjected to pressure processing, it is possible to suppress the transfer of the surface shape of the release sheet (irregularities caused by the surface roughness) to the workpiece. As a result, a molded product can be obtained with high precision and good reproducibility. Methods for controlling the surface roughness Ra to 0.05 μm or less include employing a structure having structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide as the structure of the release sheet, and appropriately controlling the conditions for forming the sheet (particularly the imidization conditions). The details of the method for measuring the surface roughness Ra are as described in the Examples.
[0033] The release sheet has a tensile modulus of elasticity of 6 GPa or more. The tensile modulus is preferably 6.5 GPa or more, and more preferably 7 GPa or more. In view of the difficulty of production, the tensile modulus is preferably 30 GPa or less, and more preferably 25 GPa or less. Since the tensile modulus is 6 GPa or more, the mechanical strength is good. Therefore, when the release sheet is sandwiched between the workpiece and a press plate or the like and subjected to pressure processing, deformation is unlikely to occur even if it is used repeatedly. As a result, even if it is used repeatedly, a molded product can be obtained with high precision and good reproducibility. Methods for controlling the tensile modulus to 6 GPa or more include employing a structure having structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide as the structure of the release sheet, and appropriately controlling the conditions for forming the sheet (particularly the imidization conditions). The details of the method for measuring the tensile modulus are as described in the Examples. In this specification, the tensile modulus refers to the average value in the MD and TD directions.
[0034] The release sheet satisfies the following formula (1). 100×|A1-A2| / A0<0.004 Formula (1) (Here, A0 is the dimension of the polyimide-containing heat-resistant release sheet at 25°C before heating, A1 is the dimension when heated from 25°C to 150°C and returned to 25°C, and A2 is the dimension when, after measuring the dimension A1, it is heated again to 150°C and returned to 25°C.) That is, the difference (absolute value) between the dimension (A1) after the first heating and cooling and the dimension (A2) after the second heating and cooling of the release sheet is almost unchanged from the dimension before heating and cooling, and the dimensional change due to moisture evaporation is small. If the release sheet contains a lot of moisture, the first heating and cooling will cause the moisture to evaporate, resulting in a large change in the dimensions of the release sheet. On the other hand, the second heating and cooling will occur after the moisture has evaporated, so the dimensional change will be smaller and the value of "100 x |A1 - A2| / A0" will be larger. However, since the release sheet according to the present embodiment contains a small amount of moisture, the value of "100 x |A1-A2| / A0" is less than 0.04. The value of "100 x |A1-A2| / A0" is preferably 0.0038 or less, and more preferably 0.0035 or less. There is no particular lower limit, but if the application is molding or lamination processing, it may be 0.0005 or more, or even 0.001 or more. Since the value of "100 x |A1-A2| / A0" is less than 0.04, when the release sheet is sandwiched between the workpiece and a press plate or the like and subjected to pressure processing, moisture evaporates from the release sheet when the temperature rises, which can suppress the accompanying dimensional changes. As a result, it is possible to suppress the workpiece from being pulled by the release sheet, which can cause wrinkles, etc. Methods for controlling the value of "100 x |A1-A2| / A0" to less than 0.04 include employing a structure having structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide as the structure of the release sheet, and setting the imidization conditions to the ranges described below. The method for determining the value of "100 x |A1-A2| / A0" is described in detail in the Examples. In this specification, the measurement value in the MD direction is used to calculate the above-mentioned "100 x |A1-A2| / A0". If the MD and TD directions are unknown, measurements are taken in two directions, and the larger value is considered to be the MD direction.
[0035] The release sheet preferably has a linear expansion coefficient (CTE) of 6 ppm / K or less, more preferably 5.5 ppm / K or less, and even more preferably 5 ppm / K or less. The lower limit of the linear expansion coefficient (CTE) is not particularly limited, but for molding and lamination processing applications, it is -10 ppm / K or more, -5 ppm / K or more, etc. When the linear expansion coefficient (CTE) is 6 ppm / K or less, it can be said that the dimensional stability (heat resistance) is more excellent. As a result, a molded product can be obtained with higher accuracy and better reproducibility. Methods for controlling the coefficient of linear expansion (CTE) to 6 ppm / K or less include employing a structure having structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide as the structure of the release sheet, and appropriately controlling the tension applied to the film during imidization. In this specification, the coefficient of linear thermal expansion refers to the average value of the values in the MD and TD directions of the release sheet.
[0036] The release sheet preferably has a melting point of 250°C or higher, more preferably 300°C or higher, and even more preferably 400°C or higher. When the melting point is 250°C or higher, the heat resistance is more excellent. In addition, the release sheet preferably has a glass transition temperature of 200°C or higher, more preferably 320°C or higher, and even more preferably 380°C or higher. When the glass transition temperature is 200°C or higher, the heat resistance is more excellent. In this specification, the melting point and the glass transition temperature are determined by differential thermal analysis (DSC). When the melting point exceeds 500°C, the thermal deformation behavior when heated at the corresponding temperature is visually observed to determine whether the melting point has been reached.
[0037] The amount of the solvent (amount of remaining solvent) contained in the release sheet is preferably 0.01 to 10 ppm, more preferably 0.01 to 5 ppm, and even more preferably 0.01 to 1 ppm. The smaller the amount of the solvent (amount of remaining solvent), the better, but in consideration of ease of production, cost, and the like, it is sufficient to set the amount to an extent that does not substantially cause problems, and the lower limit thereof is specifically 0.01 ppm. The amount of remaining solvent is measured by gas chromatography. Specifically, the amount of remaining solvent in the release sheet is quantified and measured by the following method. First, the release sheet to be measured is sampled to a size of about 10 mg, and its mass is accurately measured. After the measurement, the sample is filled into a glass insert for gas chromatography, and the glass insert is set in the inlet of a gas chromatograph equipped with a packed column. While maintaining the inlet temperature at 350°C, the inlet is purged with nitrogen carrier gas for 30 minutes, and the vaporized solvent component is trapped in the packed column at room temperature. The trapped matter is directly subjected to gas chromatography analysis using an FID detector, and the amount of remaining solvent in the measured film is quantified by the direct calibration curve method. The standard liquid used to create the calibration curve is water or methanol, which is spiked into the inlet and measured in the same manner as the film. The measurement conditions for the gas chromatograph are shown below. [Measurement conditions] Equipment: Shimadzu GC14A Separation column: 3 mm inner diameter x 1.6 m glass Filler: TENAX-TA Carrier gas: N2, 40ml / min. Inlet temperature: 350℃ Oven temperature: Room temperature trap 30 minutes → 80 to 250℃ (15℃ / min.)
[0038] The method for adjusting the amount of the remaining solvent contained in the release sheet to a predetermined range is not particularly limited, but can be controlled by the drying conditions of the green film, which is the precursor of the release sheet, and the like.
[0039] As described above, the release sheet can be obtained by applying a polyamic acid (polyimide precursor) solution obtained by reacting biphenyltetracarboxylic dianhydride (tetracarboxylic acid) and diaminobenzanilide (diamine) in a solvent to a support for producing a polyimide film, drying the solution to form a green film (also referred to as a "polyamic acid film"), and further subjecting the green film to high-temperature heat treatment on the support for producing a polyimide film or in a state where the green film has been peeled off from the support to cause a dehydration ring-closing reaction. Alternatively, a polyimide solution obtained by a dehydration ring-closing reaction between biphenyltetracarboxylic dianhydride (tetracarboxylic acid) and diaminobenzanilide (diamine) in a solvent is applied to a support for preparing a polyimide film, followed by drying to obtain a polyimide film containing, for example, 1 to 50 mass % of a solvent, and the polyimide film containing 1 to 50 mass % of a solvent is further subjected to high-temperature treatment and dried on the support for preparing a polyimide film or in a state where it has been peeled off from the support.
[0040] The solvent used when obtaining polyamic acid by polymerizing biphenyltetracarboxylic dianhydride and diaminobenzanilide is not particularly limited as long as it dissolves both the raw material monomer and the resulting polyamic acid, but a polar organic solvent is preferred, such as N-methyl-2-pyrrolidone, N-acetyl-2-pyrrolidone, N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, hexamethylphosphoric amide, ethyl cellosolve acetate, diethylene glycol dimethyl ether, sulfolane, halogenated phenols, etc. Among them, N-methyl-2-pyrrolidone and N,N-dimethylacetamide are preferably used. These solvents can be used alone or in combination. The amount of the solvent used may be sufficient to dissolve the raw material monomer, and a specific amount used is such that the mass of the monomer in the solution in which the monomer is dissolved is usually 5 to 40 mass%, preferably 10 to 20 mass%.
[0041] The polyamic acid can be produced by a known production method. That is, one or more tetracarboxylic anhydride components (including biphenyltetracarboxylic dianhydride) and one or more diamine components (including diaminobenzanilide) are used as raw materials, and polymerized in the solvent to obtain a polyamic acid solution. The reaction apparatus is preferably equipped with a temperature control device for controlling the reaction temperature, and the reaction temperature is preferably 0°C to 80°C, and more preferably 15°C to 60°C, because this suppresses hydrolysis of the polyamic acid, which is a reverse reaction of the polymerization, and also because the viscosity of the polyamic acid is easily increased.
[0042] If necessary, an imidization catalyst, inorganic fine particles, etc. may be added to the polyamic acid solution.
[0043] As the imidization catalyst, a tertiary amine is preferably used. As the tertiary amine, a heterocyclic tertiary amine is preferably used. Preferable specific examples of the heterocyclic tertiary amine include pyridine, 2,5-diethylpyridine, picoline, quinoline, and isoquinoline. The amount of the imidization catalyst used is preferably 0.01 to 2.00 equivalents, more preferably 0.02 to 1.20 equivalents, relative to the reaction site of the polyamic acid (polyimide precursor). When the amount of the imidization catalyst used is 0.01 equivalents or more, the effect of the catalyst can be sufficiently obtained. In addition, when the amount of the imidization catalyst used is 2.00 equivalents or less, the proportion of the catalyst not involved in the reaction can be reduced, which is preferable in terms of cost.
[0044] Examples of the inorganic fine particles include inorganic oxide powders such as fine silicon dioxide (silica) powder and aluminum oxide powder, and inorganic salt powders such as fine calcium carbonate powder and calcium phosphate powder. If the inorganic fine particles are present as coarse particles, they may cause defects in the subsequent steps, and therefore the inorganic fine particles are preferably uniformly dispersed in the polyamic acid solution.
[0045] The polyamic acid (polyimide precursor) solution or the polyimide solution can be applied by appropriately using a conventionally known solution application means such as spin coating, doctor blade, applicator, comma coater, screen printing, slit coating, reverse coating, dip coating, curtain coating, or slit die coating.
[0046] The reduced viscosity (ηsp / C) of the polyamic acid solution or polyimide solution is preferably 0.1 or more, more preferably 1 or more, and even more preferably 2 or more. Also, it is preferably 5 or less, more preferably 4.5 or less, and even more preferably 4 or less.
[0047] As for the drying conditions for obtaining the green film (drying conditions for the coated polyamic acid), for example, when N,N-dimethylacetamide is used as a solvent, the drying temperature is preferably 70 to 130°C, more preferably 80 to 125°C, and further preferably 85 to 120°C. By setting the drying temperature at 130°C or less, it is possible to prevent the molecular weight from decreasing and the green film from becoming brittle. In addition, by setting the drying temperature at 130°C or less, it is possible to prevent imidization from partially proceeding during the production of the green film, making it difficult to obtain the desired physical properties during the imidization process. In addition, by setting the drying temperature at 70°C or more, it is possible to suppress the drying time from becoming longer, the molecular weight from easily decreasing, and the deterioration of the handleability due to insufficient drying. In addition, the drying time is preferably 5 to 90 minutes, more preferably 15 to 80 minutes, although it depends on the drying temperature. By setting the drying time at 90 minutes or less, it is possible to suppress the molecular weight from decreasing and the film from becoming brittle. Furthermore, by setting the drying time to 5 minutes or more, deterioration of handleability due to insufficient drying can be suppressed. A conventionally known drying device can be used, and examples of the drying device include hot air, hot nitrogen, far infrared rays, and high-frequency induction heating.
[0048] As a specific method for imidizing the green film, it is preferable to imidize the green film by performing heat treatment in multiple steps. The number of steps is preferably 2 or more, more preferably 3 or more. The number of steps is preferably 10 or less, more preferably 5 or less. By making the number of steps 2 or more (more preferably 3 or more), it is possible to prevent the sudden evaporation of the solvent due to sudden heating. As a result, it is possible to improve the surface smoothness. In addition, by making the number of steps 2 or more (more preferably 3 or more), it becomes easier for the molecules to move, and it is possible to easily improve the molecular orientation by tension control. On the other hand, if the number of steps is too large, a temperature range in which a reverse reaction is likely to occur will be used, and the mechanical properties of the resulting polyimide film may be deteriorated. Therefore, by setting the number of steps to 10 or less, it is possible to suppress the deterioration of the mechanical properties of the resulting polyimide film. When imidization (heat treatment) is carried out in three steps, the temperature and time in each step are set from the following viewpoints. First step: By appropriately removing the remaining solvent, the average thickness unevenness and surface roughness of the film are improved. Steps 1 and 2: Imidization and tension control are performed while a certain amount of solvent remains, resulting in high orientation. Also, avoid the temperature range where reverse reactions are likely to occur. Third step: The imidization is completed and the resulting termini are recoupled. Specifically, when imidization (heat treatment) is carried out in three steps, the preferred ranges of temperature and time in each step are as follows. The imidization temperature in the first step is preferably 150° C. or higher, more preferably more than 180° C., even more preferably 185° C. or higher, and particularly preferably 190° C. or higher, because the average thickness unevenness and surface roughness of the film can be improved by removing the remaining solvent. The imidization temperature in the first step is preferably 220° C. or lower, more preferably 210° C. or lower. The imidization time in the first step is preferably 1 minute or more, more preferably 2 minutes or more, and is preferably 10 minutes or less, more preferably 5 minutes or less. After the first step is completed, the second step of imidization reaction (heat treatment) is carried out. The imidization temperature in the second step is preferably higher than 220° C., more preferably 230° C. or higher, and even more preferably 240° C. or higher. The imidization temperature in the second step is preferably 280° C. or lower, and more preferably 270° C. or lower. The imidization time in the second step is preferably 1 minute or more, more preferably 2 minutes or more, and is preferably 10 minutes or less, more preferably 5 minutes or less. After the second step is completed, the third step of imidization reaction (heat treatment) is carried out. The imidization temperature in the third step is preferably higher than 280° C., more preferably 290° C. or higher, and even more preferably 295° C. or higher. The imidization temperature in the third step is preferably lower than 480° C., more preferably 400° C. or lower, and even more preferably 350° C. or lower, in order to improve the average thickness unevenness and surface roughness of the film. The imidization time in the third step is preferably 2 minutes or more, more preferably 4 minutes or more, and is preferably 20 minutes or less, more preferably 10 minutes or less. By going through the above-mentioned multiple steps, a release sheet with good average thickness unevenness and surface roughness can be obtained.
[0049] The imidization (heat treatment) is carried out by holding both ends of the film with a pin tenter or clips. In order to maintain the uniformity of the film, it is preferable to make the tension in the width direction and the length direction of the film as uniform as possible. Specifically, just before the film is subjected to the pin tenter, the both ends of the film are pressed with a brush so that the pins are uniformly pierced into the film. The brush is preferably a fibrous one that is rigid and heat resistant, and a high-strength and high-elasticity monofilament can be used. By satisfying these imidization conditions (temperature, time, tension), it is possible to obtain a release sheet (polyimide film) that suppresses the occurrence of orientation distortion inside the film (front and back and planar directions), and has the average thickness unevenness, surface roughness Ra, remaining solvent amount, etc. within a predetermined range, and sufficiently maintains mechanical properties (particularly, tensile modulus, tensile breaking strength, etc.).
[0050] The release sheet is preferably produced via a green film of polyamic acid, that is, by subjecting the green film to an imidization reaction, a release sheet having superior releasability and heat resistance can be obtained.
[0051] The release sheet is preferably a non-stretched sheet, but may be a monoaxially or biaxially stretched sheet. Here, the non-stretched sheet refers to a film obtained without intentionally applying a mechanical external force in the planar expansion direction of the film by tenter stretching, roll stretching, inflation stretching, etc.
[0052] <Method of pressurizing workpiece> The pressurizing method for a workpiece according to the present embodiment includes the steps of: The method includes a step of pressing a workpiece between polyimide-containing heat-resistant release sheets, The polyimide-containing heat-resistant release sheet is The compound has structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide, The average thickness unevenness is 5% or less. The surface roughness Ra is 0.05 μm or less. The tensile modulus is 6 GPa or more, A method for pressurizing a workpiece, characterized in that the following formula (1) is satisfied: 100×|A1-A2| / A0<0.004 Formula (1) (Here, A0 is the dimension of the polyimide-containing heat-resistant release sheet at 25°C before heating, A1 is the dimension when heated from 25°C to 150°C and returned to 25°C, and A2 is the dimension when, after measuring the dimension A1, it is heated again to 150°C and returned to 25°C.)
[0053] The polyimide-containing heat-resistant release sheet used in the pressure processing method for a workpiece according to this embodiment has already been described, and therefore will not be described here.
[0054] The pressure processing method for a workpiece according to this embodiment includes a step of applying pressure to the workpiece while the workpiece is sandwiched between the polyimide-containing heat-resistant release sheets.
[0055] The workpiece is not particularly limited as long as it can be processed by pressure, and examples thereof include resin-made objects.
[0056] The pressure processing includes molding processing and lamination processing. In the case of molding processing, a molded product can be obtained by pressing (and heating as necessary) a molded object (workpiece). In the case of lamination processing, a laminate (molded product) can be obtained by pressing (and heating as necessary) two or more laminated objects (workpieces) in a stacked state.
[0057] Examples of devices for performing molding and lamination include the hot plate press method and the double belt method. In the case of the hot plate press method, a pair of the polyimide-containing heat-resistant release sheets are used as carrier sheets (transport sheets), and the workpiece is sandwiched between these carrier sheets, which are then fed into a heated press and pressed for a predetermined time. In the case of the double belt method, the polyimide-containing heat-resistant release sheet and the workpiece are continuously fed between a pair of endless steel belts, and are heated and pressed while being moved while sandwiched between the belts.
[0058] According to the method for pressurizing a workpiece according to the present embodiment, the polyimide-containing heat-resistant release sheet is used during pressurization, so that a molded product can be obtained with high precision and good reproducibility. EXAMPLES
[0059] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.
[0060] <Preparation Example 1: Preparation of polyamic acid solution 1> After replacing the inside of a reaction vessel equipped with a nitrogen inlet tube, a reflux tube, and a stirring rod with nitrogen, 22.73 parts by mass of 4,4'-diaminobenzanilide (DABAN), 201.1 parts by mass of N,N-dimethylacetamide (DMAc), and a dispersion (Nissan Chemical Industries' "Snowtex (registered trademark) DMAC-ST-ZL") in which colloidal silica (lubricant) was dispersed in dimethylacetamide were added so that the colloidal silica (lubricant) was 0.4 mass% of the total polymer solid content in the polyamic acid solution, and completely dissolved. Next, 22.73 parts by mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added in portions as a solid, and then stirred at room temperature for 24 hours. Then, 173.1 parts by mass of DMAc was added to dilute, and polyamic acid solution 1 with a solid content (NV) of 12 mass% and a reduced viscosity (ηsp / C) of 3.10 dl / g was obtained.
[0061] <Preparation Example 2: Preparation of polyamic acid solution 2> After replacing the nitrogen in a vessel equipped with a nitrogen inlet tube, a thermometer, and a stirring rod, 4,4'-diaminodiphenyl ether (ODA) was added. Next, DMAc was added and completely dissolved, and then pyrrolimetic anhydride (PMDA) was added to polymerize ODA and PMDA as monomers in a molar ratio of 1 / 1 in DMAc, so that the monomer charge concentration became 15 mass%, and the mixture was stirred at 25°C for 5 hours to obtain a brown viscous polyamic acid solution 2. The reduced viscosity (ηsp / C) was 2.1 dl / g.
[0062] <Preparation Example 3: Preparation of polyamic acid solution 3> ODA was added to DMAc at 60 mol% based on the total diamines and dissolved, followed by paraphenylenediamine (1,4-phenylenediamine) P-PDA (40 mol%) and PMDA, which were then added in sequence and stirred at room temperature for about 1 hour. Finally, a solution with a polyamic acid concentration of 20 mass% was prepared, consisting of tetracarboxylic dianhydride components and diamine components at a stoichiometric ratio of about 100 mol%. This polyamic acid solution was ice-cooled, and acetic anhydride and β-picoline were added and stirred to obtain polyamic acid solution 3.
[0063] <Preparation Example 4: Preparation of polyamic acid solution 4> After replacing the atmosphere in a vessel equipped with a nitrogen inlet tube, a thermometer, and a stirring rod with nitrogen, P-PDA was poured in. Next, DMAc was added and completely dissolved, and then PMDA was added to polymerize P-PDA and PMDA as monomers in a molar ratio of 1.0 / 1.0 in DMAc, so that the monomer charge concentration was 15 mass%, and the mixture was stirred at 25°C for 5 hours to obtain a brown viscous polyamic acid solution 4.
[0064] <Preparation Example 5: Preparation of Polyamic Acid Solution 5> After replacing the inside of a reaction vessel equipped with a nitrogen inlet tube, a thermometer, and a stirring rod with nitrogen, 500 parts by mass of 5-amino-2-(p-aminophenyl)benzoxazole was charged. Next, 5000 parts by mass of N-methyl-2-pyrrolidone was added and completely dissolved, and 40.5 parts by mass (containing 8.1 parts by mass of silica) of Snowtex (trade name) DMAc-Zl (manufactured by Nissan Chemical Industries, Ltd.) in which colloidal silica was dispersed in dimethylacetamide was added, and 485 parts by mass of pyromellitic dianhydride was added, and the mixture was stirred at a reaction temperature of 25°C for 48 hours, to obtain a pale yellow viscous polyamic acid solution 5. The reduced viscosity (ηsp / C) of the obtained solution was 4.2 dl / g.
[0065] <Preparation Example 6: Preparation of Polyamic Acid Solution 6> After replacing the inside of a reaction vessel equipped with a nitrogen inlet tube, reflux tube, and stirring rod with nitrogen, 11.36 parts by mass of 4,4'-diaminobenzanilide (DABAN), 11.32 parts by mass of 2,2'-bis(trifluoromethyl)benzidine (TFMB), 201.1 parts by mass of N,N-dimethylacetamide (DMAc), and a dispersion (Nissan Chemical Industries, Ltd.'s "Snowtex (registered trademark) DMAC-ST-ZL") in which colloidal silica (lubricant) was dispersed in dimethylacetamide were added so that the silica (lubricant) was 0.4% by mass based on the total amount of polymer solids in the polyamic acid solution, and completely dissolved. Next, 22.73 parts by mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added in portions as a solid, and the mixture was stirred at room temperature for 24 hours. Thereafter, 173.1 parts by mass of DMAc was added for dilution to obtain a polyamic acid solution 6 having a solid content (NV) of 12% by mass and a reduced viscosity (ηsp / C) of 3.28 dl / g.
[0066] <Preparation Example 7: Preparation of polyamic acid solution 7> After replacing the inside of a reaction vessel equipped with a nitrogen inlet tube, a thermometer, and a stirring rod with nitrogen, 930 parts by mass of 1,3-bis(4-aminophenoxy)benzene was added, 15,000 parts by mass of N,N-dimethylacetamide was introduced, and the mixture was stirred well to make it uniform. Then, 40.5 parts by mass (containing 8.1 parts by mass of silica) of Snowtex (trade name) DMAc-Zl (manufactured by Nissan Chemical Industries, Ltd.) in which colloidal silica was dispersed in dimethylacetamide was added. The solution was cooled to 0°C, and 990 parts by mass of 4,4'-oxydiphthalic anhydride was added, followed by stirring for 17 hours. A pale yellow viscous polyamic acid solution 7 was obtained. The reduced viscosity (ηsp / C) of the obtained solution was 3.1 dl / g.
[0067] <Preparation Example 8: Preparation of polyimide solution 1> In a reaction vessel equipped with a nitrogen inlet tube, a Dean-Stark tube, a reflux tube, a thermometer, and a stirrer, 19.86 parts by mass of 4,4'-diaminodiphenylsulfone (4,4'-DDS), 4.97 parts by mass of 3,3'-diaminodiphenylsulfone (3,3'-DDS), and 80 parts by mass of gamma-butyrolactone (GBL) were added while introducing nitrogen gas. Then, 31.02 parts by mass of 4,4'-oxydiphthalic acid non-dihydrate (ODPA), 24 parts by mass of GBL, and 13 parts by mass of toluene were added at room temperature, and the internal temperature was raised to 160°C and heated to reflux at 160°C for 1 hour to perform imidization. After completion of imidization, the temperature was raised to 180°C, and the reaction was continued while drawing out toluene. After reaction for 12 hours, the oil bath was removed and the temperature was returned to room temperature, and GBL was added so that the solid content became 20 mass %. Polyimide solution 1 having a reduced viscosity of 0.70 (ηsp / C) dl / g was obtained.
[0068] <Preparation Example 9: Preparation of polyimide solution 2> A reaction vessel equipped with a nitrogen inlet tube, a Dean-Stark tube, a reflux tube, a thermometer, and a stirrer was charged with nitrogen gas, and 230 parts by mass of N,N-dimethylacetamide (DMAc) was added to 32.02 parts by mass of 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl (TFMB) and completely dissolved. Next, 44.42 parts by mass of 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride (6FDA) was added in portions as a solid (molar ratio of 6FDA / TFMB = 1.00 / 1.00), and the mixture was stirred at room temperature for 24 hours. This resulted in a polyamic acid solution with a solid content of 25% by mass and a reduced viscosity of 1.10 dl / g. Next, 204 parts by mass of DMAc was added to the obtained polyamic acid solution to dilute the polyamic acid concentration to 15% by mass, and then 1.3 parts by mass of isoquinoline was added as an imidization catalyst. Next, while stirring the polyamic acid solution, 12.25 parts by mass of acetic anhydride was slowly dropped as an imidization agent. After that, the mixture was stirred for 24 hours to carry out a chemical imidization reaction, and a polyimide solution was obtained. Next, 100 parts by mass of the obtained polyimide solution was transferred to a reaction vessel equipped with a stirring device and a stirrer and stirred at a speed of 120 rpm. Next, 150 parts by mass of methanol was slowly dropped therein, and precipitation of powdery polyimide was confirmed. The contents were then filtered off by suction filtration and washed with methanol. The filtered polyimide powder was dried in a dryer at 50°C for 24 hours and then further dried at 260°C for 5 hours to obtain the desired polyimide powder. 20 parts by mass of the obtained polyimide powder was dissolved in 80 parts by mass of DMAc, and a dispersion obtained by dispersing colloidal silica (lubricant) in dimethylacetamide (Nissan Chemical Industries, Ltd.'s "Snowtex (registered trademark) DMAC-ST-ZL") was further added so that the silica (lubricant) accounted for 1.4 mass% of the total polymer solid content in the polyimide solution, thereby obtaining a uniform polyimide solution 2.
[0069] <Example 1: Production of polyimide film F1> The polyamic acid solution 1 was coated on the non-slip surface of a polyethylene terephthalate film A4100 (support made by Toyobo Co., Ltd.) using a comma coater, adjusting the final film thickness to 15 μm. The polyethylene terephthalate film A4100 passed through a hot air oven and was wound up, during which it was dried at 100 ° C for 10 minutes. The polyamic acid film (green film) that had obtained self-supporting properties after drying was peeled off from the support, passed through a pin tenter having a pin sheet with pins arranged thereon, and the film end was held by inserting it into the pins, and the pin sheet interval was adjusted so that the film would not break and unnecessary slack would not occur, and the film was conveyed while being heated under the conditions of 200 ° C for 3 minutes, 250 ° C for 3 minutes, and 300 ° C for 6 minutes to allow the imidization reaction to proceed. After that, it was cooled to room temperature in 2 minutes, and the parts of the film with poor flatness at both ends were cut off with a slitter, and the film was wound up into a roll, obtaining 500 m of polyimide film F1 with a width of 450 mm.
[0070] <Example 2: Production of polyimide film F2> A polyimide film F2 was obtained in the same manner as in Example 1, except that the polyamic acid solution 1 was changed to the polyamic acid solution 6.
[0071] <Example 3: Production of polyimide film F10> The polyamic acid solution 1 was coated on the non-slip surface of a polyethylene terephthalate film A4100 (support manufactured by Toyobo Co., Ltd.) using a comma coater, with the final film thickness adjusted to 15 μm. The polyethylene terephthalate film A4100 was passed through a hot air oven and wound up, during which it was dried at 100 ° C for 10 minutes. The polyamic acid film (green film) that had obtained self-supporting properties after drying was peeled off from the support, passed through a pin tenter having a pin sheet with pins arranged thereon, and the film end was held by inserting it into the pins, and the pin sheet interval was adjusted so that the film would not break and unnecessary slack would not occur, and the film was conveyed while being heated under the conditions of 210 ° C for 2 minutes, 260 ° C for 2 minutes, and 330 ° C for 5 minutes to allow the imidization reaction to proceed. After that, it was cooled to room temperature in 2 minutes, and the parts of the film with poor flatness at both ends were cut off with a slitter, and the film was wound up into a roll, to obtain 500 m of polyimide film F10 with a width of 450 mm.
[0072] <Example 4: Production of polyimide film F11> A polyimide film F11 was obtained in the same manner as in Example 3, except that the polyamic acid solution 1 was changed to the polyamic acid solution 6.
[0073] <Comparative Example 1: Production of Polyimide Film F3> The polyamic acid solution 2 was coated on the non-slip surface of a polyethylene terephthalate film A4100 (support manufactured by Toyobo Co., Ltd.) using a comma coater, with the final film thickness adjusted to 15 μm. The polyethylene terephthalate film A4100 was passed through a hot air oven and wound up, during which it was dried at 100 ° C for 10 minutes. The polyamic acid film (green film) that had obtained self-supporting properties after drying was peeled off from the support, passed through a pin tenter having a pin sheet with pins arranged thereon, and the film end was held by inserting it into the pins, and the pin sheet interval was adjusted so that the film would not break and unnecessary slack would not occur, and the film was conveyed while being heated under the conditions of 180 ° C for 3 minutes, 250 ° C for 3 minutes, and 480 ° C for 5 minutes to allow the imidization reaction to proceed. After that, it was cooled to room temperature in 2 minutes, and the parts of the film with poor flatness at both ends were cut off with a slitter, and the film was wound up into a roll, to obtain 500 m of polyimide film F3 with a width of 450 mm.
[0074] <Comparative Example 2: Production of Polyimide Film F4> A polyimide film F4 was obtained in the same manner as in Comparative Example 1 for the polyimide film F3, except that the polyamic acid solution 2 was changed to the polyamic acid solution 3.
[0075] <Comparative Example 3: Production of Polyimide Film F5> A polyimide film F5 was obtained in the same manner as in Comparative Example 1 for the polyimide film F3, except that the polyamic acid solution 2 was changed to the polyamic acid solution 4.
[0076] <Comparative Example 4: Production of Polyimide Film F6> The polyimide solution 1 was coated on the non-slip surface of a polyethylene terephthalate film A4100 (support made by Toyobo Co., Ltd.) using a comma coater, with the final film thickness adjusted to 15 μm. The polyethylene terephthalate film A4100 was passed through a hot air oven and wound up, during which it was dried at 100 ° C for 10 minutes. The solvent-containing polyimide film (green film) that had obtained self-supporting properties after drying was peeled off from the support, passed through a pin tenter having a pin sheet with pins arranged thereon, and the film end was held by inserting it into the pins, and the pin sheet interval was adjusted so that the film would not break and unnecessary slack would not occur, and the film was conveyed, heated at 200 ° C for 3 minutes, 250 ° C for 3 minutes, and 300 ° C for 6 minutes, and dried. After that, it was cooled to room temperature in 2 minutes, and the parts of the film with poor flatness at both ends were cut off with a slitter, and the film was wound up into a roll, to obtain 500 m of polyimide film F6 with a width of 450 mm.
[0077] <Comparative Example 5: Production of Polyimide Film F7> Polyimide film F7 was obtained in the same manner as polyimide film F6, except that polyimide solution 1 was changed to polyimide solution 2.
[0078] <Comparative Example 6: Production of Polyimide Film F8> A polyimide film F8 was obtained in the same manner as in Comparative Example 1, except that the polyamic acid solution 1 was used.
[0079] <Comparative Example 7: Production of Polyimide Film F9> A polyimide film F8 was obtained in the same manner as in Comparative Example 1, except that polyamic acid solution 6 was used.
[0080] <Preparation of thermoforming sheet (workpiece)> The above polyamic acid solution 7 was coated onto the non-lubricant side of a 188 μm thick polyethylene terephthalate film A4100 (manufactured by Toyobo Co., Ltd.) using a comma coater (gap: 200 μm, coating width: 700 mm), dried at 110° C. for 5 minutes, and then the polyamic acid film was rolled up without peeling it off from the support. The obtained polyamic acid film was attached to the unwinding section of a film-forming machine, and the above polyamic acid solution 5 was coated onto the surface of the polyamic acid film 7 using a comma coater (gap: 800 μm, coating width: 700 mm). After drying at 110° C. for 20 minutes, the polyamic acid film was wound up without peeling it off from the support. The obtained polyamic acid film was again attached to the unwinding section of the film-forming machine, and the above polyamic acid solution 7 was coated onto the surface of the polyamic acid film 5 using a comma coater (gap: 200 μm, coating width: 700 mm), and dried for 5 minutes at 110° C. After drying, the film was peeled off from the support to obtain a polyamic acid film (green film) having a three-layer structure of (polyamic acid 7) / (polyamic acid 5) / (polyamic acid 7). The multilayer polyamic acid film was passed through a pin tenter having three heat treatment zones, and heat-treated at 150°C for 2 minutes in the first stage, 220°C for 2 minutes in the second stage, and 475°C for 4 minutes in the third stage. The film was then slit into a width of 500 mm to obtain a thermoforming sheet having a thickness of 50 μm. The thickness ratio of (polyamic acid 7) / (polyamic acid 5) / (polyamic acid 7) in this thermoforming sheet was 0.25 / 1 / 0.25. The thermoforming sheet obtained was embedded in epoxy resin, cut with a microtome so that the cross section could be observed, and the cross section was observed with a transmission electron microscope. In the electron microscope image of the cross section, the boundary between layers with different compositions could be observed in a striped manner, and the thickness ratio was almost the same as the thickness ratio obtained from the coating thickness. The sheet was slit into a width of 450 mm and used for thermoforming.
[0081] <Reduced viscosity (ηsp / C) of polyamic acid solution and polyimide solution> A solution of the polymer dissolved in N-methyl-2-pyrrolidone to a polymer concentration of 0.2 g / dl was measured at 30° C. using an Ubbelohde type viscometer.
[0082] <Average thickness unevenness> The average thickness unevenness of the polyimide films of the Examples and Comparative Examples was determined by the following method. <How to determine the average thickness unevenness: When the release sheet is in roll form> A rectangular sample was cut from the center of the transverse direction (TD). The size of the rectangular sample was 5 cm wide and 5 cm long. Then, four rectangular samples were cut at 1 m intervals in the longitudinal direction (MD), to obtain a total of five samples. For each strip, the thickness was measured at a total of five points: the center, two points 5 cm apart from the center along the length, and two points 10 cm apart from the center. For each strip, the thickness unevenness was calculated using the following calculation. Thickness unevenness = 100 x (maximum thickness - minimum thickness) / (average thickness) Finally, the thickness variations of the five strips were averaged, and this was taken as the average thickness variation value. <How to calculate the average thickness unevenness: When the release sheet is rectangular (sheet)> The thickness was measured at five locations in total: four corners and one in the center. The four corners were measured at a distance of 10 cm from the two adjacent sides. The thicknesses at the five locations were averaged, and this was taken as the average thickness unevenness. The thickness at each point was measured using a micrometer (Militron 1254D, manufactured by Feinluf Co., Ltd.). The results are shown in Table 1.
[0083] <Surface roughness Ra> The surface roughness Ra of the polyimide films of the examples and comparative examples was determined by the following method. The measurements were made using a stylus surface roughness meter (Mitutoyo Corporation, SV-C3100S4) in accordance with the center line average roughness (hereinafter referred to as Ra) in JIS B0601:2013 (Definition and display of surface roughness). Measurements were made at r tip 2 μm and λ c 0.8 mm. The results are shown in Table 1.
[0084] <Tensile modulus of release sheet (polyimide film)> The tensile modulus of elasticity of the polyimide films of the Examples and Comparative Examples was determined by the following method. The dried film was cut into strips of 100 mm length and 10 mm width in the longitudinal direction (MD) and transverse direction (TD) to prepare test pieces, and the tensile modulus was measured using a tensile tester (Shimadzu Corporation Autograph (product name) model name AG-5000A) at a tension speed of 50 mm / min and a chuck distance of 40 mm. The temperature during measurement was 25°C. Measurements were carried out in the MD and TD directions, and the average value was taken as the tensile modulus. The results are shown in Table 1.
[0085] <Calculation of 100×|A1-A2| / A0> The 100×|A1−A2| / A0 of the polyimide films of the Examples and Comparative Examples was determined by the following method. The dimensional change rate in the MD direction of each of the polyimide films to be measured was measured under the following conditions. (When the polyimide film is in roll form) A rectangular sample was cut from the center of the transverse direction (TD). The size of the rectangular sample was 10 mm wide and 100 mm long. Then, four rectangular samples were cut at 1 m intervals in the longitudinal direction (MD), to obtain a total of five samples. Each sample was further cut into a sample length of 10 mm and a sample width of 2 mm. The dimensions of the polyimide film (strip) before heating were measured at room temperature (25° C.) and designated as A0 (10 mm). Next, the polyimide film was heated from 25° C. to 150° C., and the dimensions when returned to 25° C. were measured, and these were designated as A1. Next, the polyimide film after the measurement of the dimension A1 was heated again to 150° C., and the dimension after returning to 25° C. was measured, and this was designated as A2. Then, 100×|A1-A2| / A0 was calculated. This was performed for five strips, and the average value of 100×|A1−A2| / A0 was taken as the value of 100×|A1−A2| / A0 for the polyimide films of the Example and Comparative Example. (When the polyimide film is rectangular (sheet)) Strip-shaped samples were cut from a total of five locations: four corner locations and one in the center. The size of the strips was 10 mm wide and 100 mm long. The four corner samples were cut from a strip centered 20 mm from the edge in the width direction. Then, 100×|A1−A2| / A0 was calculated using the method described above. This was performed for five strips, and the average value of 100×|A1−A2| / A0 was taken as the value of 100×|A1−A2| / A0 for the polyimide films of the Example and Comparative Example. Device name: BRUKER TMA4000SA Sample length: 10 mm Sample width: 2mm Heating start temperature: 25℃ End temperature of heating: 150℃ Hold time at temperature rise end: 30 min Heating rate: 20℃ / min Cooling rate: 5℃ / min Atmosphere: Argon The samples were conditioned at 23°C and 50% RH for at least 24 hours before use. The results are shown in Table 1.
[0086] <Coefficient of linear thermal expansion (CTE) of release sheet (polyimide film)> The coefficient of linear thermal expansion (CTE) of the polyimide films of the Examples and Comparative Examples was determined by the following method. For the release sheet (polyimide film) to be measured, the dimensional change rate in the MD and TD directions was measured under the following conditions, and the dimensional change rate / temperature was measured at 30°C to 45°C, 45°C to 60°C, ... and 15°C intervals. This measurement was performed up to 300°C, and the average value of all measured values was calculated as CTE. Device name: MAC Science TMA4000S Sample length: 20mm Sample width: 2mm Heating start temperature: 25℃ Heating end temperature: 400℃ Heating rate: 5℃ / min Atmosphere: Argon The results are shown in Table 1.
[0087] <Measurement of glass transition temperature of release sheet (polyimide film)> The glass transition temperatures of the polyimide films of the Examples and Comparative Examples were determined by the following method. Measurement was performed using a differential scanning calorimeter (DSC-200, SII). 5 mg of a sample (polyimide film) was placed in an aluminum lid-type container and crimped to seal it. First, the temperature was raised from room temperature (25°C) to 550°C at 20°C / min. In the endothermic curve obtained during this process, the glass transition temperature was determined as the temperature at the intersection of the extension of the baseline before the endothermic peak (below the glass transition temperature) and the tangent to the endothermic peak (the tangent showing the maximum slope between the rising part of the peak and the apex of the peak). The results are shown in Table 1. In Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 5, and Comparative Example 6, glass transition did not occur even at 500° C., and when the temperature was further increased, thermal decomposition occurred first, so that the glass transition temperature could not be measured.
[0088] <Evaluation of use as a release sheet (surface smoothness of molded object and release sheet condition after use)> The polyimide film of the examples and comparative examples was slit to a width of 450 mm to prepare two sheets, which were used as release sheets. Five sheets of the thermoforming sheets obtained in the above <Preparation of Thermoforming Sheets> were sandwiched between these two release sheets, and hot and pressure molding was continuously performed by hot plate pressing. As the hot plate pressing conditions at this time, a hot plate pressing part with a width of 470 mm and a length of 300 mm was adopted, and the production was performed with a heating temperature of 320°C, a pressing pressure of 40 MPa, and a pressing time of 3 minutes per press. After each press, the sheet was sent out by about 150 mm, and a polyimide molded sheet with a length of about 3 m was produced in about 60 minutes. The polyimide molded sheet produced using the polyimide film of Example 1 had excellent surface smoothness, and the thickness of any portion was measured to be approximately 250 μm, which was almost uniform. The produced polyimide molding sheet was peeled into a thermoforming sheet and a release sheet, and the surface smoothness of the surface of the thermoforming sheet (molded object) that had been in contact with the release sheet and the state of the surface of the release sheet that had been in contact with the thermoforming sheet (state of the release sheet after use) were observed. Here, if the surface smoothness and the state of the release sheet after use are good, it can be said that the releasability of the molded object is good. The surface smoothness of the thermoforming sheets was evaluated by checking the surface condition of the thermoforming sheets and the presence or absence of peeling between the thermoforming sheets when the cross-sections of the thermoforming sheets were observed under a microscope. Those with no problems were rated as ◎, those with slight surface abnormalities or peeling were rated as △, and those with abnormalities in both the surface condition and peeling were rated ×. Specifically, the surface was observed at 10 points at 100x magnification using a Keyence VH-Z100R. For cross-sectional observation, one side of the polyimide molding sheet and the thermoforming sheet (the side not in contact with the thermoforming sheet or the polyimide molding sheet, respectively) was protected with resin, and then a cross-section was prepared using a microtome. The prepared cross-section was observed at 10 points at 100x magnification using a Nikon differential interference microscope. In addition, the state of the release sheet after use was observed and rated as follows: absolutely no defects such as wrinkles or cracks, ⊚; slightly no defects, Δ; and many defects, ×. The results are shown in Table 1.
[0089] [Table 1]
Claims
1. The compound has structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide, The average thickness unevenness is 5% or less, The surface roughness Ra is 0.05 μm or less, The tensile modulus is 6 GPa or more, A polyimide-containing heat-resistant release sheet, characterized in that the following formula (1) is satisfied: 100×|A1-A2| / A0<0.004 Formula (1) (Here, A0 is the dimension of the polyimide-containing heat-resistant release sheet at 25° C. before heating, A1 is the dimension when heated from 25° C. to 150° C. and returned to 25° C., and A2 is the dimension when, after measuring the dimension A1, it is heated again to 150° C. and returned to 25° C.)
2. 2. The polyimide-containing heat-resistant release sheet according to claim 1, wherein the linear thermal expansion coefficient is 6 ppm / K or less.
3. The method includes a step of pressing a workpiece between polyimide-containing heat-resistant release sheets, The polyimide-containing heat-resistant release sheet is The compound has structural units derived from biphenyltetracarboxylic dianhydride and diaminobenzanilide, The average thickness unevenness is 5% or less, The surface roughness Ra is 0.05 μm or less, The tensile modulus is 6 GPa or more, A method for pressurizing a workpiece, characterized in that the following formula (1) is satisfied: 100×|A1-A2| / A0<0.004 Formula (1) (Here, A0 is the dimension of the polyimide-containing heat-resistant release sheet at 25° C. before heating, A1 is the dimension when heated from 25° C. to 150° C. and returned to 25° C., and A2 is the dimension when, after measuring the dimension A1, it is heated again to 150° C. and returned to 25° C.)
Citation Information
Patent Citations
Polyimide film and its production
JP1990150453A
Mold release sheet
JP2000062089A
Mold release sheet
JP2000290897A
Heat-resistant release sheet and method for manufacturing the sheet
JP2003127267A
Polyimide film and copper-clad laminate using the same as base material
JP2009067859A